A framework for measuring quality improvement in Irish supplier SMEs: a multiple case analysis. (1st September 2004) - McAdam, Rodney; McEnroe, Catherine
The aim of this paper is to build a framework for Quality Process Monitoring and Improvement for SMEs which requires a minimal outlay of resources, and which does not rely on the implementation of external or formal programmes. The Irish economy is heavily dependent on the continual emergence and development of indigenous SMEs. If such SMEs are to grow and prosper they must continuously apply contemporary business improvement methodologies. Existing approaches, such as the Business Excellence Model, have been developed based on the assumptions of large-scale organisations. In many cases they are ill-suited to scarce resource environment of SMEs. There is, therefore, a need for a low resource framework for quality improvement in SMEs. The research methodology involves a multiple case analysis of supplier SMEs. The findings indicate that a low resource for quality improvement can assist SMEs in meeting customer requirements and in lowering costs.